Half‐Graben Rupture Geometry of the 30 October 2016 MW 6.6 Mt. Vettore‐Mt. Bove Earthquake, Central Italy. Issue 4 (11th April 2019) - Cheloni, D.; Falcucci, E.; Gori, S.
Abstract: Existing models for the rupture geometry and slip distribution associated with the 30 October MW 6.6 Mt. Vettore‐Mt. Bove earthquake in central Italy show significant dissimilarities. Indeed, due to the quite complicated observed deformation pattern, the activation of a complex multifault structure during a single seismic event was invoked. In this study, we explore different rupture scenarios and we develop a robust model of the rupture process of the 30 October earthquake, designed from new field observations, aftershock distribution, and static coseismic offsets including new near‐field survey‐mode global position system measurements, regional Global Positioning System observations, Interferometric Synthetic Aperture Radar interferograms, and static displacements derived from strong‐motion stations. Our preferred best fit model involves the simultaneous rupture of the master Mt. Vettore‐Mt. Bove normal fault and of at least two secondary antithetic faults (as they significantly contributed to the total deformation field), which overall describe a "simple conceptual" half‐graben normal fault system and whose arrangement fits the geological, seismological, and coseismic evidence of surface faulting. Notably, our model fits the geometry of seismogenic structures defined prior to the 2016–2017 seismic sequence by field Quaternary geological observations. In addition, no significant coseismic slip on faults alternative to the master and antithetic faults is necessary to explain the observed surface displacements during the 30 October Mt. Vettore‐Mt. Bove earthquake. Key Points: We revisit the rupture geometry of the MW 6.6 30 October 2016 earthquake in central Italy The earthquake ruptured both the master normal fault system and the antithetic faults on the opposite side of the Castelluccio plain No significant coseismic slip on faults alternative to the master and antithetic faults is necessary to reproduce the surface displacements